Signal hijacking and ROS attack antibacterial strategy using QS-interfering aptamer and bimetallic MOF - Kuaile Wu; Mengxia Duan; Yalin Mo; Man Ding; Ning Ma; Zhouping Wang; Shijia Wu; Nuo Duan (Chemical Engineering Journal, 2026)

Combined exposure to hypoxia and 17α-ethinylestradiol alters reproductive traits in marine medaka - Xian Qin; Jiezhang Mo; Huiju Lin; Yi Yang; Emily Sze Wan Wong; Min Pan; Sidney Man Ngai Chan; Rudolf Shiu Sun Wu; William Ka Fai Tse; Keng Po Lai (Aquatic Toxicology, 2026)

Association between amygdala subregions and non-motor symptoms in Parkinson’s disease: a fixel-based analysis - Yuchen She; Jiahao Wei; Junyi Wang; Ying Liu; Sicheng Chen; Man Zhang; Qi Yang; Lijuan Mo; Changhong Tan; Xi Liu; Lifen Chen (Brain Imaging and Behavior, 2026)

Petrology, geochemistry and geochronology of the Kekeya ash (SW Tarim Basin): Implications for its origin and provenance - Jia-Jun Mo; Yu-Ting Zhong; Man Wang; Le Zhang; Qiong Wu; Qiang Ma; He Wang; Jahandar Ramezani; Xiao-Long Huang; Fu-Yuan Wu; Yi-Gang Xu (Lithos, 2026)

Ab initio calculations of the structural, electronic and mechanical properties of palygorskite under high pressure - Changhui Song; Jinchong Gan; Jing Zou; Man Mo; Zhijie Fang; Haitao Wang (Applied Clay Science, 2025)

Comparative study on the structural, antioxidant and functional properties of hydrolysates from Pleurotus erynigii and Pleurotus ostreatus protein by alcalase and trypsin - Xiao-Xuan Hou; Shu-Jing Bing; Man Hao; Jie Yang; Gui-Jin Sun; Ying-Qiu Li; Chen-Ying Wang; Yan Liang; Hai-Zhen Mo (Food Bioscience, 2025)

Efficient separation of impurities from pyrolusite and the enhancement of its products for improving the performance of lithium-ion batteries - Riran Zang; Houyang Chen; Shuxian Shi; Man mo; Dawei Lan; Guangliang Zhang; Yangxian Huang; Kunsong Hu; Xinghua Liang; Lingxiao Lan; Yong Yang; Junji Li; et al. (Chemosphere, 2025)

Glycolysis-regulating polyphenol nanoparticles restore immune homeostasis and tolerance in autoimmune multiple sclerosis - Ngoc Man Phan; Dong Kwang Min; Xin Wang Mo; Pilseon Im; Jaeyun Kim (Chemical Engineering Journal, 2025)

The Guanylate Cyclase Soluble Subunit Alpha-1 Deficiency Impairs Angiogenesis in Zebrafishes and Mice: In Vivo and In Vitro Studies - Man Luo; Dongcan Mo; Jianli Li; LiuYu Liu; Xiaoling Li; Jing Lin; Jie Liang; Fei Ye; Xiaozuo Lin; Pingkai Wang; Xiaoju Wu; Yinan Zeng; et al. (Molecular Neurobiology, 2025)

Spatial distribution, chemical speciation and source apportionment of carbon, nitrogen and phosphorus in surface sediments of northern Beibu Gulf, South China - Jing Guo; Xiaomin Yan; Man Wu; Hengtong Qiu; Wan-Yi Li; Wenlong Huang; Di Wu; Baoming Xue; Guilin Xu; Zihan Pan; Zhiming Mo (Marine Pollution Bulletin, 2024)

Application of Cytochrome P450 Monooxygenases in Plant for Rapid Detection of 2,3,7,8 Tetrachlorodibenzodioxin in the Contaminated Sites - Ho Man Leung; Ka Chun Sung; Lai Yan Woo; Wing Yin Mo; Kwai Chung Cheung; Chi Kin Au; Ken Kin Lam Yung; Wai Chin Li (International Journal of Environmental Research, 2024)

Assessment of Spatial Variability of Polycyclic Aromatic Hydrocarbons (PAHs) in Urban Soils and Fungal Disease Status of Trees Grown in Hong Kong Areas - Ka Chun Sung; Ho Man Leung; Chi Fung Lee; Tohidi Fatemeh; Wing Yin Mo; Lai Yan Woo; Kwai Chung Cheung; Uchenna Ogbonnaya; Ken Kin Lam Yung; Wai Chin Li (International Journal of Environmental Research, 2024)

Angiotensin-Converting Enzyme Insertion/Deletion Polymorphism and the Risk of Leukoaraiosis in a South Chinese Han Population: A Case–Control Study - Dong-can Mo; Xiao-ju Wu; Xiao-ling Li; Liu-yu Liu; Yi-ying Jiang; Guo-qiu Zhou; Li-jie Chen; Jiao-xing Li; Man Luo (Biochemical Genetics, 2024)

Quasi-closed-loop approach for facile and environmentally friendly red mud reutilization as advanced Li-ion anode material - Dawei Lan; Yixun Gu; Xianglong Chen; Man Mo; Zhijie Fang; Panyu Xiong; Weichi Ye; Gangli Zhao; Tianshi Xiong; Minfeng Huang; Weijian Li; Haiqing Zhan; et al. (Journal of Cleaner Production, 2024)

Research development on electrolytes for magnesium-ion batteries - Yuehua Man; Pauline Jaumaux; Yifan Xu; Yating Fei; Xiangyin Mo; Guoxiu Wang; Xiaosi Zhou (Science Bulletin, 2023)

Ultrasensitive fluorescence detection of multiple DNA methyltransferases based on DNA walkers and hyperbranched rolling circle amplification - Siqi Zhang; Huahao Shao; Kai-Bin Li; Wei Shi; Yichao Wang; De-Man Han; Jinggang Mo (Analytica Chimica Acta, 2023)

In-depth numerical analysis of combustion and NOx emission characteristics in a 125 MWe biomass boiler - Viet Thieu Trinh; Seung-Mo Kim; Kang-Min Kim; Byoung-Hwa Lee; Tae-Yong Jeong; Ju-Seong Son; Jong-Man Kim; Chung-Hwan Jeon (Fuel, 2023)

LINC00152 mediates CD8+ T-cell infiltration in gastric cancer through binding to EZH2 and regulating the CXCL9, 10/CXCR3 axis - Jinqing Ou; Pingguang Lei; Zhenling Yang; Man Yang; Lingmin Luo; Hongdan Mo; Guijin Luo; Junhui He (Journal of Molecular Histology, 2021)

Feasibility of Sijunzi Tang (Chinese medicine) to enhance protein disulfide isomerase activities for reactivating malate dehydrogenase deactivated by polycyclic aromatic hydrocarbons - Ho Man Leung; Francis Siu Lai Kwok; Wing Yin Mo; Kwai Chung Cheung; Yik Kit Yue; Yee Keung Wong; Chi Kin Au; Martin Tsz Ki Tsui; Ken Kin Lam Yung (Environmental Science and Pollution Research, 2021)

Patterns and networks of language control in bilingual language production - Qiming Yuan; Junjie Wu; Man Zhang; Zhaoqi Zhang; Mo Chen; Guosheng Ding; Chunming Lu; Taomei Guo (Brain Structure and Function, 2021)

Associations between SNP83 of phosphodiesterase 4D gene and carotid atherosclerosis in a southern Chinese Han population: a case–control study - Liu-yu Liu; Dong-can Mo; Jian-li Li; Yi-ying Jiang; Guo-qiu Zhou; Dong-dong Jiang; Li-jie Chen; Xiao-ju Wu; Jiao-xing Li; Man Luo (Mammalian Genome, 2021)

Use of biochar as feed supplements for animal farming - Ka Yan Man; Ka Lai Chow; Yu Bon Man; Wing Yin Mo; Ming Hung Wong (Critical Reviews in Environmental Science and Technology, 2021)

Direct and indirect effects of microplastics on bivalves, with a focus on edible species: A mini-review - Feng Zhang; Yu Bon Man; Wing Yin Mo; Ka Yan Man; Ming Hung Wong (Critical Reviews in Environmental Science and Technology, 2020)

Ecological risks of heavy metals/metalloid discharged from two sewage treatment works to Mai Po Ramsar site, South China - Yu Bon Man; Kim Man Lei; Ka Lai Chow; Anna Oi Wah Leung; Wing Yin Mo; Ming Hung Wong (Environmental Monitoring and Assessment, 2020)

Screening for antagonistic bacteria against Fusarium oxysporum and their influence on the consecutive monoculture problem of Rehmannia glutinosa - Jia-fang Du; Xuan-zhen Li; Man-yu Liu; Zhong-yi Zhang; Mo Wang (Journal of Plant Pathology, 2020)

Application of Spirulina in aquaculture: a review on wastewater treatment and fish growth - Feng Zhang; Yu Bon Man; Wing Yin Mo; Ming Hung Wong (Reviews in Aquaculture, 2020)
There is an urgent need to find alternatives to fish meal and fish oil in compound feeds due to their rapidly rising prices and the demand for sustainable fisheries. Spirulina, a filamentous blue‐green microalga, is an excellent source of plant protein and could replace expensive animal‐derived proteins in fish feed. Studies have evaluated the use of spirulina as a fish meal for different fish species. This paper reviews research on the effects of spirulina on the growth performance of various fish species. It is apparent that spirulina can be a highly important component of the diet of fish; it has a number of benefits, such as promoting the growth of tilapia ( Oreochromis niloticus ) and carp ( Labeo rohita ), improving the reproductive performance of yellow tail cichlid ( Pseudotropheus acei ) and enhancing the immune response of rainbow trout ( Oncorhynchus mykiss ). Recent studies have shown that spirulina can be used for treating wastewater, including effluent from fish culture activities, as it can efficiently metabolize the nutrients and remove the heavy metals contained in aquaculture effluent. Fish aquaculture could apply an integrated strategy of simultaneously treating aquaculture effluent while producing spirulina biomass to supplement fish diets.

Sorption of Pb in chemical and particle-size fractions of soils with different physico-chemical properties - Hyun-Jung Park; Hyun-Jin Park; Hye In Yang; Se-In Park; Sang-Sun Lim; Jin-Hyeob Kwak; Goon-Taek Lee; Sang-Mo Lee; Man Park; Woo-Jung Choi (Journal of Soils and Sediments, 2019)

Sorption-desorption behaviors of heavy metals by biochar-compost amendment with different ratios in contaminated wetland soil - Zhaoxue Yang; Jie Liang; Lin Tang; Guangming Zeng; Man Yu; Xiaodong Li; Xuemei Li; Yingying Qian; Haipeng Wu; Yuan Luo; Dan Mo (Journal of Soils and Sediments, 2018)

Application of veterinary antibiotics in China’s aquaculture industry and their potential human health risks - Wing Yin Mo; Zhanting Chen; Ho Man Leung; Anna Oi Wah Leung (Environmental Science and Pollution Research, 2017)

Food wastes as fish feeds for polyculture of low-trophic-level fish: bioaccumulation and health risk assessments of heavy metals in the cultured fish - Zhang Cheng; Cheung-Lung Lam; Wing-Yin Mo; Xiang-Ping Nie; Wai-Ming Choi; Yu-Bon Man; Ming-Hung Wong (Environmental Science and Pollution Research, 2016)

The use of food waste-based diets and Napier grass to culture grass carp: growth performance and contaminants contained in cultured fish - Zhang Cheng; Wing-Yin Mo; Xiang-Ping Nie; Kai-Bing Li; Wai-Ming Choi; Yu-Bon Man; Ming-Hung Wong (Environmental Science and Pollution Research, 2016)

Use of food waste as fish feeds: effects of prebiotic fibers (inulin and mannanoligosaccharide) on growth and non-specific immunity of grass carp (Ctenopharyngodon idella) - Wing Y. Mo; Zhang Cheng; Wai M. Choi; Clare H. I. Lun; Yu B. Man; James T. F. Wong; Xun W. Chen; Stanley C. K. Lau; Ming H. Wong (Environmental Science and Pollution Research, 2015)

IAA Producing Enterobacter sp. I-3 as a Potent Bio-herbicide Candidate for Weed Control: A Special Reference with Lettuce Growth Inhibition - Jae-Man Park; Ramalingam Radhakrishnan; Sang-Mo Kang; In-Jung Lee (Indian Journal of Microbiology, 2015)

Environmental mercury concentrations in cultured low-trophic-level fish using food waste-based diets - Zhang Cheng; Wing Yin Mo; Yu Bon Man; Cheung Lung Lam; Wai Ming Choi; Xiang Ping Nie; Yi Hui Liu; Ming Hung Wong (Environmental Science and Pollution Research, 2015)